Microphysical and optical properties of Arctic mixed-phase clouds. The 9 April 2007 case study - Gayet, J.-F.; Mioche, G.; Dörnbrack, A.; Ehrlich, A.; Lampert, A.; Wendisch, M. (Atmospheric Chemistry and Physics, 2009)
Airborne measurements in Arctic boundary-layer stratocumulus were carried out near Spitsbergen on 9 April 2007 during the Arctic Study of Tropospheric Aerosol, Clouds and Radiation (ASTAR) campaign. A unique set of co-located observations is used to describe the cloud properties, including detailed in situ cloud microphysical and radiation measurements along with airborne and co-located spaceborne remote sensing data (CALIPSO lidar and CloudSat radar). CALIPSO profiles indicate cloud top levels at temperature between Ã¢ÂÂ24ÃÂ°C and Ã¢ÂÂ21ÃÂ°C. In situ measurements confirm that the cloud-top lidar attenuated backscatter signal along the aircraft trajectory is linked with the presence of liquid water, a common feature observed in Arctic mixed-phase stratocumulus clouds. A low concentration of large ice crystals is also observed up to the cloud top resulting in significant CloudSat radar echoes. Since the ratio of the extinction of liquid water droplets to ice crystals is high, broadband radiative effects near the cloud top are mostly dominated by water droplets. CloudSat observations and in situ measurements reveal high reflectivity factors (up to 15 dBZ) and precipitation rates (1 mm hÃ¢ÂÂ1). This feature results from efficient ice growth processes. About 25% of the theoretically available liquid water is converted into ice water with large precipitating ice crystals. Using an estimate of mean cloud cover, a considerable value of 106 m3 hÃ¢ÂÂ1 of fresh water could be settled over the Greenland sea pool. European Centre for Medium-Range Weather Forecast (ECMWF) operational analyses reproduces the boundary layer height variation along the flight track. However, small-scale features in the observed cloud field cannot be resolved by ECMWF analysis. Furthermore, ECMWF's diagnostic partitioning of the condensed water into ice and liquid reveals serious shortcomings for Arctic mixed-phased clouds. Too much ice is modelled.